Financial Dollarization of Households and Firms : Does It Differ? - Corrales, Juan (IMF Working Papers; Working Paper ;, 2019)
Using a newly complied and extended database from International Financial Statistics, and applying different panel-regression techniques, this paper documents the evolution of households' and firms' dollarization over the past decade. We assess the macroeconomic determinants of dollarization for households and firms and explore differences between high and low-income countries. We find that households' and firms' dollarization in loans and deposits are weakly explained by the currency substitution model, except in low income countries, where inflation plays a significant role. Instead, market development variables such as financial deepening, access to external debt and FX finance as well as other market considerations are key to explain the dynamics of deposits and loans dollarization, regardless of the level of income.These factors can account for a significant fraction of the dollarization, but using a variance decomposition model, there is evidence that a non-negligible portion has yet to be explained. This suggests that there are key determinants for household and firm dollarization that are not fully captured by traditional macroeconomic explanatory variables.